Study of dissociation of Ritodrine, Phenylepherine and Midodrine and their binary complexation with M(II) ions. (4th May 2017) - Khaled, Rehab; Mohamed, F.; Moaty, S.A. Abdel
ABSTRACT: The aim of this work was to study in-depth the acid dissociation constants of Ritodrine, phenylepherine and Midodrine using the potentiometric technique in an aqueous solution and three different mixtures of water and dioxane. Also, the dissociation constants of Ritodrine, phenylepherine and Midodrine have been calculated in an aqueous medium with an ionic strength of 0.15–0.30 mol L −1 NaNO3 . The dissociation constants (pKa) values for the ionisation in a water (1) + dioxane (2) mixture have been determined at different temperatures ranging from 298.15 to 328.15 K. Then, the thermodynamic parameters ( have been examined and discussed. The ligation action of ligands was studied in order to get an idea about their potentiality towards some transition metals in vitro systems. The formation of binary complexes of [Cu +2, Co +2, Cd +2, Ni +2, Mn +2 and Zn +2 ] with Ritodrine, phenylepherine and Midodrine has been studied by pH-metric titrations at 37.0 ± 0.1°C and with an ionic strength of I  = 0.15 mol L −1 (NaNO3 ) in an aqueous solution. Along with their overall stability, constants were taken by the HYPERQUAD 2008 program from the potentiometric data. The thermodynamic parameters were determined and discussed for Cu +2 –L (L: Ritodrine, phenylepherine and Midodrine). The formation in the binary and ternary complexes of the Cu +2, Co +2 and Ni +2 metal ion with aromatic acid (anthranilic acid and 5-sulfosalicylic acid and phenylepherine) was estimated by means of potentiometry and conductometry at 37°C and in I  = 0.15 mol. Results showed that L −1 NaNO3 was with stoichiometric coefficients 1:1:1. The ternary system formation has been displayed in a stepwise mechanism. The stability constants of these ternary systems have been calculated and discussed. The concentration distributions of the various complex species in solution have been evaluated and discussed.